Returns to Education and Overeducation Risk: A Dynamic Model - Lorenzo Navarini; Dieter Verhaest (Global Labor Organization (GLO), 2024)
When individuals risk being overeducated for their jobs, returns to education might be lower and heterogeneous. To investigate this, we develop a novel framework that decomposes returns using an expected value conditional on overeducation risks and penalties. We estimate these components using Belgian data and a dynamic model of endogenous educational choices, overeducation, and wages. Our findings reveal that overeducated individuals experience a persistent wage penalty. However, as both medium and higher levels of education are associated with an overeducation risk, this risk usually plays a limited role in explaining average returns. Moreover, consistent with job polarization, this role is even positive for Bachelor's degrees as these degrees rather reduce the overeducation risks and the associated penalties. Finally, we find that overeducation generates heterogeneous realized returns among Master's graduates.
Keywords: 330; Skill Mismatch; Overeducation; Dynamic Discrete Choice Model; Heterogeneous Returns to Education; Educational Expansion